An update on the nomenclature for cutaneous vasculitis. Issue 1 (January 2019) - Caproni, Marzia; Verdelli, Alice
Abstract : Purpose of review: Cutaneous vasculitis reflects a spectrum ranging from skin limited to severe systemic forms. To date, there is still no generally acknowledged nomenclature for cutaneous vasculitis. This review aims to summarize the recent advances in the nomenclature of cutaneous vasculitis. Recent findings: The most widely adopted vasculitis classification system is the one of 2012 Revised Chapel Hill Consensus Conference (CHCC) which represent not such a classification but a nomenclature system that name vasculitis on the basis of the size of the vessel affected. The CHCC 2012 did not deal with the special features of cutaneous vasculitis and did not explicitly discuss the presence of skin-limited or skin-dominant forms of vasculitis. Therefore, a consensus group was formed to propose an Addendum to CHCC 2012, focusing on cutaneous vasculitis. The Addendum better clarify the main aspects of some single-organ vasculitis, including IgM/IgG vasculitis, nodular vasculitis, erythema elevatum et diutinum and recurrent macular vasculitis in hypergammaglobulinemia. Moreover, it differentiated normocomplementemic from hypocomplementemic urticarial vasculitis. Finally, it recognized cutaneous polyarteritis nodosa as a distinct subtype of polyarteritis nodosa. Summary: Classification criteria are useful tools to standardize names and definitions for cutaneous vasculitis; however, they do not represent diagnostic criteria. Collaborative efforts are still needed to get a shared classification and valid diagnostic criteria for cutaneous vasculitis.